Lucky Boy - Boase, Susan (Boston : Houghton Mifflin, 2002)
A neglected dog finds a real home with a grieving widower who needs a friend.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Grief -- Fiction